Assessment of potential habitat suitability for kiwifruit (Actinidia spp) in Shaanxi Province under climate change scenarios - Niu, Zhen; Han, Dong; Niu, Zijie; Roussos, Petros A.; Cheng, Tao; Xie, Jiyuan; Cao, Geni; Liu, Dandan; Jin, Ning; Zhang, Dongyan (Frontiers in Plant Science, 2025)
IntroductionClimate change and anthropogenic activities have significantly altered the distribution patterns of kiwifruit resources in Shaanxi Province. Clarifying the characteristics of future climate suitability zones can provide scientific support for optimizing industrial planning and mitigating meteorological disaster risks.MethodsThis study applied the MaxEnt model with ENMeval package parameter optimization. Environmental factor contributions were quantified via jackknife tests, and spatial consistency between major producing counties and ecological suitability areas was analyzed using ArcGIS. The dynamic shifts and centroid migration patterns of kiwifruit habitats under four Shared Socioeconomic Pathways (SSP) climate scenarios (SSP126, SSP245, SSP370, SSP585) during the 2050–2070 were simulated.Results and discussionCurrently, high-suitability zones (13,100 km², 6.38% of the province) are concentrated in the northern Qinling Mountains, Weihe River terrace irrigation areas, and the Danjiang/Hanjiang River basins of southern Shaanxi, while moderate-suitability zones cover 32,600 km² (15.86%). Critical environmental drivers include the mean temperature of the coldest quarter, elevation, annual temperature variation range, and soil moisture content. Future projections reveal substantial reductions in high-suitability habitats (SSP126: 79.12% decrease to 2,700 km² by 2080; SSP245/370/585 reductions of 58.01%/68.33%/61.70%), intensified habitat fragmentation, and slight northwestward centroid shift. This study systematically evaluates climate change impacts on kiwifruit suitability zones, offering a theoretical basis for intensive adjustments in Shaanxi’s cultivation zones, agricultural policy formulation, and biodiversity conservation strategies.